Multigenerational exposure of microplastics on the microbiota of E. affinis (copepod): a comparative study between biodegradable and nonbiodegradable microplastics - Thery, Jérémy; Li, Luen-Luen; Das, Shagnika; Dufour, Dylan; Benali, Samira; Raquez, Jean-Marie; Souissi, Sami; Monchy, Sébastien (Frontiers in Ecology and Evolution, 2023)
Accumulation of plastics debris in the world, especially in marine environment has been well documented during the past decades. Recent studies have found that inorganic surfaces of microplastics (MPs) can be used by microorganisms as living substrates and form an ecosystem named "plastisphere". Some microorganisms present on MPs are capable to produce polymers-degrading enzymes. In addition, MPs can also serve as vectors and carry microorganisms (including potential pathogens) into higher trophic levels through their ingestion by animals. In this study, impacts on copepod's microbiota during chronic exposure of MPs were investigated by exposing copepods to a classic single-use polymer (low density polyethylene -LDPE) and a biodegradable polymer (polybutylene adipate terephthalate -PBAT). Copepods were exposed to "virgin" and "weathered" MPs during four generations at an environmentally relevant concentration of 300µg/L, followed by one "detoxification" generation without MPs exposition. Impacts of MPs-exposure on copepods microbiota were investigated using 16S rRNA gene high-throughput sequencing. The result of nonmetric multidimensional scaling (NMDS) analysis showed that copepods (with or without MPs exposure) carried distinguishable microbiota as compared with microbiota of water and microalgae used for maintaining copepods. According to results of permutational analysis of variance (PERMANOVA) analysis, microbiota of MPs-exposed (both PBAT and LDPE) copepods were significantly different from microbiota of un-exposed copepods during generations 1 to 4. After "detoxification" however, no significant difference in microbiota composition was observed among all generation 5 copepods. Altogether, impacts on copepods microbiota of MPs exposure for multiple Microplastics effects on copepods microbiota 2 generations were observed, in spite of plastics origin (biodegradable or not) and aging conditions. Furthermore, copepod microbiota seemed to be returned to their original structure as soon as the MPs exposure stopped.